PENGARUH UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - I Gusti Ngurah Satria Wijaya (Unitri Press, 2019)
This study aims to know the size of the company against firm value with capital structure as an intervening variable on the Indonesia Stock Exchange. The data used in this study are secondary data from telecommunications sector companies on the Indonesia Stock Exchange. The analysis technique used in this study is multiple linear regression and multiple analysis for the influence of indirect factors. The results show that there are positive effect of company size on firm value, capital structure has no significant positive effect on firm value, and capital structure is not able to mediate the effect of firm size with firm value. For investors to pay attention to company size factors to the value of the company to invest in a company and for future researchers to use a longer year of research and a larger number of samples so that the results obtained are close to actual.